The lack of discursive opportunities when becoming a mathematics teacher - Ebbelind, Andreas; Lutovac, Sonja (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
In this paper, we attempt to open a discussion about mathematics teacher education settings constraining prospective teachers’ discursive opportunities, a phenomenon noted in our respective doctoral dissertations. These two doctoral dissertations represent two different types of prospective teachers from three countries. Prospective primary school teachers who had positive experiences and interest in mathematics on the one hand, and prospective teachers who struggled with mathematics and were insecure about their future mathematics teaching on the other. In the discussion, we speculate about the implications of discursive opportunities for prospective teachers’ process of becoming a mathematics teacher and highlight the need to place effort to offer sufficient discursive opportunities to prospective teachers.